EFEKTIFITAS TEKNIK COUNTERPRESSURE DALAM MENGURANGI NYERI PERSALINAN KALA I DI PMB S KOTA BEKASI TAHUN 2023 - Khoiriah, Restu (Politeknik Tiara Bunda, 2023)
Introduction: Labor is the process of opening and thinning the cervix, as well as uterine contractions, and the fetus descending into the birth canal, causing pain in labor. Labor pain is a physiological process as many as 12%-67% of women feel worried about the pain that will be experienced during labor. Efforts to reduce labor pain are counterpressure techniques. Objectives: to determine the effectiveness of counterpressure techniques to reduce pain in the first stage of labor in the Independent Practice of the Sutra Midwife Des Kelissa Kel. West Bekasi District Officer in 2022. Methods: This study used a quasi-experimental (quasi-experimental) method with a two-Group posttest only design which was divided into two groups, namely the control group and the intervention group. The sampling technique in this study used a total sampling of 30 mothers giving birth in the first stage of the active phase and each 15 people in the control group and 15 people in the intervention group. Data were collected using observation sheets and analyzed using the Mann Withney U test. Results: The study showed that the counterpressure technique was more effective in reducing the level of pain in active phase maternity mothers as indicated by the p-value = (0.005) <0.05, meaning that there was a difference in pain scale between the intervention group and the control group. Conclusion: The counterpressure technique is a good alternative that needs to be recommended to reduce pain intensity in active phase I birth mothers.